Sustainability Practices as Mediator of Internal and External Drivers on Food and Beverage SME Business Performance - Maria Kristiana; Elok Savitri Pusparini (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: The growing activities of SMEs increase energy consumption and waste, creating environmental challenges. Therefore, SMEs need to adopt sustainability practices, although their effectiveness depends on internal and external factors. Objective: This study examines how internal factors, including top management support, organizational resources, and green open innovation, as well as external factors, such as green supplier collaboration, influence the business performance of small and medium-sized enterprises (SMEs) in the food and beverage (F&B) sector in the Greater Jakarta Area (Jabodetabek), with sustainability practices serving as a mediating variable. This sector was selected due to its important contribution to the national economy and the urgent need to address its environmental impacts. Methods: Employing a confirmatory quantitative approach with a cross-sectional research design, data collected from 215 SME managers were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). This study provides a novel integration of internal and external sustainability drivers with sustainability practices as a mediator of business performance in F&B SMEs. The respondents consisted primarily of small-business managers (72.1%) with 3–5 years of managerial experience operating in the Greater Jakarta Area (Jabodetabek). Results: Organizational resources demonstrated the strongest total effect on business performance (Beta = 0.518), followed by top management support (Beta = 0.446). Green supplier collaboration exhibited full mediation, indicating that its influence on business performance occurs entirely through sustainability practices. Meanwhile, internal factors demonstrated partial mediation effects. Conclusion: This study extends RBT by showing that sustainability practices act as dynamic capabilities that enhance business performance through internal capabilities and supplier collaboration.